Semantic web services, processes and applications (Springer, 2006)
The book provides the semantic enabling of all phases of semantic Web processes. This encompasses design, annotation, discovery, choreography and composition. Also this book presents fundamental capabilities and techniques associated with ontological modeling or services, annotation, matching and mapping, and reasoning. This is complemented by discussion of applications in e-Government and bioinformatics